CD133+ cells contribute to radioresistance via altered regulation of DNA repair genes in human lung cancer cells - Desai, Amar (2014)
BACKGROUND: Radioresistance in human tumors has been linked in part to a subset of cells termed cancer stem cells (CSCs). The prominin 1 (CD133) cell surface protein is proposed to be a marker enriching for CSCs. We explore the importance of DNA repair in contributing to radioresistance in CD133+ lung cancer cells. MATERIALS AND METHODS: A549 and H1299 lung cancer cell lines were used. Sorted CD133+ cells were exposed to either single 4Gy or 8Gy doses and clonogenic survival measured. γ-H2AX immunofluorescence and quantitative real time PCR was performed on sorted CD133+ cells both in the absence of IR and after two single 4Gy doses. Lentiviral shRNA was used to silence repair genes. RESULTS: A549 but not H1299 cells expand their CD133+ population after single 4Gy exposure, and isolated A549 CD133+ cells demonstrate IR resistance. This resistance corresponded with enhanced repair of DNA double strand breaks (DSBs) and upregulated expression of DSB repair genes in A549 cells. Prior IR exposure of two single 4Gy doses resulted in acquired DNA repair upregulation and improved repair proficiency in both A549 and H1299. Finally Exo1 and Rad51 silencing in A549 cells abrogated the CD133+ IR expansion phenotype and induced IR sensitivity in sorted CD133+ cells. CONCLUSIONS: CD133 identifies a population of cells within specific tumor types containing altered expression of DNA repair genes that are inducible upon exposure to chemotherapy. This altered gene expression contributes to enhanced DSB resolution and the radioresistance phenotype of these cells. We also identify DNA repair genes which may serve as promising therapeutic targets to confer radiosensitivity to CSCs.